SEG Technical Program Expanded Abstracts 2009 2009
DOI: 10.1190/1.3255143
|View full text |Cite
|
Sign up to set email alerts
|

Using continuous microseismic records for hydrofracture diagnostics and mechanics

Abstract: Using continuous microseismic records is a novel technique for better understanding the mechanics of the fracture network evolution during a hydrofracture treatment, and to provide a tool for diagnostic evaluation of recorded microseismic data. Hydrofracture stimulations are widely used during well completions to optimize production volumes and extraction rates in petroleum reservoirs, enhanced geothermal systems and block-caving mines. Microseismic monitoring is now becoming a standard tool for evaluating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…For example, Long‐Period and Long‐Duration events (LPLD) are detected after band passing the recorded data based on the frequency content of the different observed signals (microseismic events, ambient noise...) obtained using the Short‐Time Fourier Transform (STFT) [ Das and Zoback , ]. Likewise, Pettitt et al [] try to incorporate in a single framework the microseismicity, hydraulic treatment conditions, and data frequency content. They observe resonance frequencies during and between microseismic experiments with variations in amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Long‐Period and Long‐Duration events (LPLD) are detected after band passing the recorded data based on the frequency content of the different observed signals (microseismic events, ambient noise...) obtained using the Short‐Time Fourier Transform (STFT) [ Das and Zoback , ]. Likewise, Pettitt et al [] try to incorporate in a single framework the microseismicity, hydraulic treatment conditions, and data frequency content. They observe resonance frequencies during and between microseismic experiments with variations in amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…Stepwise relative location (Reyes-Montes et al, 2009a) allows a more accurate source location within the observed MS cluster (and thus a more accurate analysis of the fracture network itself), as the technique depends only on the seismic velocity in the im- Pettitt et al, 2009) F r a c t u r e s mediate volume of the cluster rather than the velocity structure through the geological formation to the receivers. The approach uses a lattice of well-located master events along a developing hydrofracture to relatively locate target events with lower signal-tonoise and that may consist of only S-wave arrivals.…”
Section: Enhanced Microseismic Analysis (Ema)mentioning
confidence: 99%
“…Analysis of fracture network connectivity and structure uses interpretation of the location data combined with algorithms that utilize amplitude information and source parameters processed from the waveforms. Pettitt et al (2009) investigate this additional amplitude information through analysis of continuous microseismic records. The case studies presented utilized the continuous streams of MS amplitude data recorded during the hydraulic treatments of oilbearing reservoirs and illustrated that both P-and S-waves can only be identified for a small fraction of the seismic record, with most released seismic energy appearing as single phase triggers in the record (Figure 6).…”
Section: Enhanced Microseismic Analysis (Ema)mentioning
confidence: 99%
“…On the other hand, continuous recordings and their timefrequency analysis also provide valuable information as illustrated by Das and Zoback (2011) and Pettitt et al (2009). Das and Zoback (2011) use the short-time Fourier transform (STFT) to design a band-pass filter in order to remove background noise and undesired signals.…”
Section: Introductionmentioning
confidence: 99%